2022
DOI: 10.1002/edm2.385
|View full text |Cite
|
Sign up to set email alerts
|

Medium‐chain Acyl‐COA dehydrogenase deficiency: Pathogenesis, diagnosis, and treatment

Abstract: Introduction Medium‐Chain Acyl‐CoA Dehydrogenase Deficiency (MCADD) is the most common inherited metabolic disorder of β‐oxidation. Patients with MCADD present with hypoketotic hypoglycemia, which may quickly progress to lethargy, coma, and death. Prognosis for MCADD patients is highly promising once a diagnosis has been established, though management strategies may vary depending on the severity of illness and the presence of comorbidities. Methods and Results Given the rapid developments in the world of gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 75 publications
(227 reference statements)
1
8
0
Order By: Relevance
“…Cellular oxidative stress and defense-mechanism-related metabolites such as oxidized lipids and glutathione were significantly affected. Some of our findings have been reported previously [1,28]; however, for the first time, we reported that the DBS from MCADD newborns had elevated glutathione and had altered certain types of oxidized lipids, notably those not reported before, which is suggestive of increased oxidative stress events. These findings may be used as potential biomarkers for MCADD as a complementary diagnostic approach in addition to the most currently known acylcarnitine biomarkers.…”
Section: Untargeted Metabolomics As a Complementary Diagnostic Approa...supporting
confidence: 78%
See 1 more Smart Citation
“…Cellular oxidative stress and defense-mechanism-related metabolites such as oxidized lipids and glutathione were significantly affected. Some of our findings have been reported previously [1,28]; however, for the first time, we reported that the DBS from MCADD newborns had elevated glutathione and had altered certain types of oxidized lipids, notably those not reported before, which is suggestive of increased oxidative stress events. These findings may be used as potential biomarkers for MCADD as a complementary diagnostic approach in addition to the most currently known acylcarnitine biomarkers.…”
Section: Untargeted Metabolomics As a Complementary Diagnostic Approa...supporting
confidence: 78%
“…Medium-chain acyl-CoA dehydrogenase deficiency (MCADD) is one of the inherited metabolic disorders (IMDs) that are associated with metabolic disturbances [1]. MCADD is the most common inherited fatty acid β-oxidation disorder, and it is caused by various genetic mutations in the acyl-CoA dehydrogenase medium chain (ACADM) gene.…”
Section: Introductionmentioning
confidence: 99%
“…MCAD is a medium-chain fatty acid oxidase, and MCAD deficiency is one of the most common mitochondrial fatty acid β-oxidation disorders[ 81 ]. MCAD deficiency prevents the dehydrogenation step of β-oxidation in the mitochondria, leading to decreased acetyl-CoA production and the accumulation of acylcarnitine caused by carnitine transport from medium-chain fatty acids, resulting in disorders of intrahepatic lipid metabolism[ 82 ]. SREBP1c is a key adipogenic transcription factor that is activated by insulin in the postprandial state.…”
Section: Discussionmentioning
confidence: 99%
“…ACADM is primarily responsible for the decomposition of medium-chain fatty acyl-CoA into short-chain fatty acyl-CoA and acetyl-CoA. When ACADM is deficient, it leads to hypoketotic hypoglycemia in neonates, which eventually leads to their death [ 31 ]. In HCC, the expression of ACADM is low.…”
Section: Discussionmentioning
confidence: 99%